Notes on genetically modified organisms, perception of their benefits, risks and potential hazards - Long, Khuat Dang (Academia Journal of Biology, 2013)
Today, modern biotechnology refers usually the use of genes, and the process of genetic modification is emerging and advancing throughout the world that created genetically modified organisms (GMOs), including GM crops or GM foods, based on the pros and cons of GM organisms came up with the controversal points, this papper discussed about why it is no wonder that genetically modified foods are surrounded by public debate and concern. Arguments for the use of GMOs were often based on their preeminent characteristics that are beneficial to human. On the contrary, with this technology being so new, long term studies have not been conducted to confirm that this process is in fact safe, the arguments against GMOs were that genes may jump from one species to another, one of the greatest concerns is the long-term health affects that genetically modified foods will have on human health. Since gene technology introduces new, exotic genes, their location within the recipient cell DNA is unpredictable and with no possibility of targeting. This may result in unpredictable effects on the metabolism, physiology and biochemistry of the recipient, transgenic organism, effects not detected with traditional methods of control. When production, marketing and consumption of GM food are highly controversial, weighing the benefits and risks associated with emerging GM foods will be necessary to understand the degree to which society embraces or rejects genetically modified foods in the future.